Influence of chronic diseases on societal participation in paid work, volunteering and informal caregiving in Europe: a 12-year follow-up study. Issue 2 (26th November 2018) - Scharn, Micky; Oude Hengel, Karen; Boot, Cécile R L; Burdorf, Alex; Schuring, Merel; van der Beek, Allard J; Robroek, Suzan J W
Abstract : Background: This study aims to provide insight into (1) the associations between having a chronic disease and participation in paid work, volunteer activities or informal care, (2) the associations between the onset of a chronic disease and these forms of societal participation, and (3) whether these associations differ across educational level and gender. Methods: The study population consisted of n=21 875 respondents of the Survey of Health, Ageing and Retirement in Europe aged between 50 years and the country-specific retirement age. The influence of having and the onset of a chronic disease on societal participation was analysed using a hybrid Poisson regression model, combining fixed and random effects, and presented by relative risks (RRs). Results: Individuals with a chronic disease were less likely to participate in paid work (RR: 0.69; 95% CI 0.67 to 0.71) and volunteer activities (RR: 0.92; 95% CI 0.88 to 0.97), but more likely to give informal care (RR: 1.05; 95% CI 1.01 to 1.08). Onset of a chronic disease was associated with a higher likelihood to quit paid work (RR: 0.91; 95% CI 0.86 to 0.97) and to give informal care (RR: 1.08; 95% CI 1.01 to 1.16). Lower educated individuals with a chronic disease or with the onset of a chronic disease were less likely to have paid work than higher educated individuals. Conclusion: Individuals with a chronic disease were less likely to participate in paid work and volunteer activities, and more likely to provide informal care. Educational inequalities were present for paid work. More insight into which factors hinder societal participation among individuals with a chronic disease is needed.